How do the wets burn? Fire behavior and intensity in wet grasslands in the Brazilian savanna - Schmidt, Isabel B.; Fidelis, Alessandra [UNESP]; Miranda, Heloísa S.; Ticktin, Tamara (Springer Nature, 2017)
Although wetlands are commonly managed with fire by local communities and managers in tropical savannas, little is known about fire behavior in these ecosystems. We measured fire intensity and temperature in 13 experimental early (June) and late (September) dry season fires in wet grasslands in the Brazilian savanna, the Cerrado. We aimed to characterize Cerrado wet grasslands fire behavior and to understand how fire season (early vs. late dry season) and time since last fire affect fire behavior and intensity. We compared fire intensities in biennially burnt areas to areas unburned for 5 years. Experimental fires consumed 60–98 % of the fuel and were of low intensity (240–1083 kW m−1) compared to those in dry savanna grassland with similar fuel loads (0.4–1.3 kg m−2). Fires in areas with contrasting times since last fire (2 and 5 years) had similar intensities. Late dry season fires tended to be more intense than early dry season fires, but the difference was not significant. The low fire intensities are probably due to high soil water availability year around, a characteristic of wetlands. Maximum temperatures were low (149–442 °C, mostly at 50 cm in height) compared to fires in dry savanna ecosystems. Our results can directly contribute to plan and implementation of fire management programs in the “Cerrado”, where it is mostly still not carried out.
Keywords: Eriocaulaceae; Fire management; Fire season; Fire temperatures; Protected areas; “Campos úmidos”; “Cerrado”